2021
DOI: 10.1016/j.gfs.2021.100497
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling heterogeneity of consumers’ food choice: Implications for nutrition interventions in eastern India

Abstract: Understanding heterogeneity of consumers' food choice is critical in formulating tailored nutrition interventions. To illustrate this, we survey urban and rural consumers from low- and middle-income households in eastern India to unravel five sources of heterogeneity (5 Ws) in gastronomic systems that affect diets: (i) socioeconomic characteristics of the target population ( who ); (ii) food environments ( where ); (iii) eating occasions ( when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In New Zealand, FE policy implementation led to excellent recommendations, such as the implementation of a national action plan for preventing non-communicable diseases, establishing priorities for reducing childhood and adolescent obesity, doubling funding for population nutrition promotion, and reducing the marketing of unhealthy foods [ 76 ]. In India, various nutrition interventions were formulated to enhance the FE through systematic planning and embracing differences in the problem for decoding and dividing to simplify resolutions to be addressed by policymakers and nutritionists in the future [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…In New Zealand, FE policy implementation led to excellent recommendations, such as the implementation of a national action plan for preventing non-communicable diseases, establishing priorities for reducing childhood and adolescent obesity, doubling funding for population nutrition promotion, and reducing the marketing of unhealthy foods [ 76 ]. In India, various nutrition interventions were formulated to enhance the FE through systematic planning and embracing differences in the problem for decoding and dividing to simplify resolutions to be addressed by policymakers and nutritionists in the future [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis can explain why interventions that improved neighbourhood food availability alone yielded inconsistent effects on food purchase and consumption (40) but showed positive results if combined with other components like food affordability and desirability (41,42) . Theoretical and empirical studies of food choice have also indicated that food purchase and consumption decisions are complex, contextual and driven by inter-related factors (43,44) . Building on these evidence, our findings support the multi-component approach in food environment interventions, where multiple aspects are taken into account to influence the overall perception of neighbourhood food access, which can lead to changes in food purchase (45) , home food availability (46) and ultimately food consumption.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus pertinent that these facets are incorporated in the policy discourse on food security. Cultural heritage defines where people purchase and consume food (food environments), when they consume it (eating occasions), what they consume (dishes, food items, beverages), how they consume it (using utensils or by hand) and why (ingredient attributes and pairings, convenience, consumer attitudes towards food) ( Custodio et al, 2021 ).…”
Section: Cultural Heritage Preference Matching and Food Securitymentioning
confidence: 99%
“…It should be acknowledged that cultural heritage does not always lead individuals towards healthier food choices. Gastronomic systems research in eastern India, for example, suggests that culturally inherited preference for starchy and oil dense rice-based diets can be a barrier for nutrition interventions that seek to encourage healthy diets ( Custodio et al, 2021 ; Samaddar et al, 2020 ). This presents a similar quandary as has been previously discussed, where culturally popular diets are less than nutritious.…”
Section: Cultural Heritage Preference Matching and Food Securitymentioning
confidence: 99%